KERJA SAMA INDONESIA DAN JEPANG DALAM PEMBANGUNAN ENERGI BARU TERBARUKAN PROYEK PEMBANGKIT LISTRIK TENAGA AIR (PLTA) RAJAMANDALA PERIODE 2012-2019 - Siti Intan Syamsiah (2020)
One important sector for a country like Indonesia is the availability of energy. Energy has a role as a fundamental and important component for human survival and development. In the national medium-term development plan (RPJMN) 2020-2024 explained that the challenges in meeting energy needs in the future is predicted to be heavier with fossil energy reserves which are depleting over time. Therefore alternative energy is needed, the addition of electricity supply in the new renewable energy sector is very important to be quickly built by the government because it is considered as part of the nation's commitment to achieving the targets set out in the National Energy General Plan of 23 percent in the year 2025, so it is important to pay attention to any new renewable energy projects that are taking place. Through cooperation between Indonesia and Japan in the construction of new renewable energy projects the Rajamandala Hydroelectric Power Plant, will increase the national electricity supply. This study aims to find out what forms of cooperation between Indonesia and Japan in the development of the Rajamandala Hydroelectric Power Plant project known to Indonesia and Japan to form and implement a Joint Venture that is part of a Foreign Direct Investment that has many innate benefits such as Investment Funding, Labor Transfer experts, to human resource development. This study uses a qualitative approach that explains and describes what forms of cooperation between Indonesia and Japan in the Development of the Renewable Energy Project of the Rajamandala Hydroelectric Power Project.